2021
DOI: 10.21037/gs-21-31
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in skeletal posture between breast reconstruction with latissimus dorsi flap and mastectomy: a prospective comparison study

Abstract: Background: The latissimus dorsi (LD) flap is used in cases of immediate breast reconstruction after total or partial mastectomy. However, studies on the effect of unilateral LD flap reconstruction on skeletal posture and comparison with results from mastectomy-only have been sparse. Thus in this prospective, observational study, we compared skeletal posture and functional recovery in patients who underwent a mastectomy-only versus those who underwent breast reconstruction with a LD flap after mastectomy.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
(18 reference statements)
0
12
1
Order By: Relevance
“…It is one of the most commonly used flaps in reconstruction of small to moderate breast volumes [20]. In a recent study, the transfer of the unilateral LD muscle to the breast, with an extended LD flap, did not interfere with shoulder function or activities of daily living [21]. In case of insufficient flap volume, additionally, a single-center uncontrolled study also demonstrated Fat-Augmented LD (FALD) a safe and reliable technique.…”
Section: Discussionmentioning
confidence: 98%
“…It is one of the most commonly used flaps in reconstruction of small to moderate breast volumes [20]. In a recent study, the transfer of the unilateral LD muscle to the breast, with an extended LD flap, did not interfere with shoulder function or activities of daily living [21]. In case of insufficient flap volume, additionally, a single-center uncontrolled study also demonstrated Fat-Augmented LD (FALD) a safe and reliable technique.…”
Section: Discussionmentioning
confidence: 98%
“…It is one of the most commonly used aps in reconstruction of small to moderate breast volumes. In a recent study, the transfer of the unilateral LD muscle to the breast, with an extended LD ap, did not interfere with shoulder function or daily life [17]. Mastectomy is a surgical treatment for breast cancer, which includes the aim of performing immediate breast reconstruction, simultaneously, after con rmation of oncological When patients have small breast volumes, total mastectomy, followed by reconstruction, is a viable option.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the IBR group showed significantly smaller changes in postoperative spinal alignment compared with the MA group. Lee et al [18] also reported that there were significant difference in the Cobb angle between the IBR and MA group when using whole spine (pre-and post-operative Cobb angle; 6.5 and 5.8 in the IBR group, 5.3 and 6.8 in the MA group). However, we should carefully consider the clinical meaning of the results in these previous studies because the value is too small despite statistical significance.…”
Section: Plos Onementioning
confidence: 92%
“…In addition, breast cancer survivors are at elevated risk for spinal abnormalities (e.g., scoliosis) because of post-treatment changes in posture and bone health. Other authors [13][14][15][16][17][18][19] have evaluated the relationship between breast cancer surgery and spine deformity by means of radiological assessment. However, the findings of these studies are inconsistent, and most studies employed chest radiographs or dual energy X-ray absorptiometry to identify only thoracic or lumbar regions of the spine.…”
Section: Introductionmentioning
confidence: 99%